Compare the effects of two silicone-hydrogel bandage contact lenses on epithelial healing after photorefractive keratectomy with anterior segment optical coherence tomography - Eliaçık, Mustafa; Karaman Erdur, Sevil; Gülkılık, Gökhan; Özsütçü, Mustafa; Karabela, Yunus (Elsevier, 2015)
Purpose: To evaluate the efficacy of two silicone hydrogel bandage lenses (SiHy) on epithelial healing following photorefractive keratectomy (PRK) with anterior segment optical coherence tomography (AS-OCT). Methods: Forty-two eyes of 21 patients who underwent PRK were included in a contralateral eye comparison study. At the end of the procedure, one eye of each patient was fitted with a Lotrafilcon B contact lens whereas the fellow eye was fitted with a Comfilicon A lens. Patients were examined on the day of surgery and at days 1-5 postoperatively. Main outcome measures were number of reepithelialized eyes, epithelial defect size, patient discomfort score and average complete reepithelization time. Results: The number of mean reepithelialized eyes was showed no statistical significance between both groups during the follow up. Average epithelial defect size for Comfilcon A and Lotrafilcon B was 32.7 +/- 12.2 mm(2) vs. 33.3 +/- 12 mm(2) at day 1 (p = 0.279) and 13.1 +/- 6 mm(2) vs. 14.5 +/- 9 mm(2) at day 3 postoperatively (p = 0.018). Average re-epithelialization time was 3.1 days for Comfilcon A and 3.6 days for Lotrafilcon B (p = 0.03). Mean subjective discomfort score was 2.25 +/- 0.96 in eyes with Lotrafilcon B and 1.64 +/- 0.67 in eyes with Comfilcon A on the first exam the day after surgery and until third day the differences were statistically significant (p = 0.011 and p = 0.012, respectively). Conclusions: AS-OCT is a reliable and noncontact method for assessment of reepithelialization under contact lenses after PRK. Eyes with Comfilcon A showed a statistically significant better discomfort score and faster reepithelialization time.
WOS: 000355824600014
PubMed ID: 25707929
Keywords: Anterior Segment Optical Coherence Tomography; Bandage Contact Lens; Photorefractive Keratectomy